Integrasi Interkoneksi Metode Bimbingan Konseling Islam Berlandaskan Hadis Nabawi - Riadatul Jannah; Irsyadunnas (DA'WA: Jurnal Bimbingan Penyuluhan & Konseling Islam, 2024)
This research aims to integrate Islamic counseling methods with an approach that combines spiritual values from prophetic traditions and modern psychological theories. The background of this research is based on the need to harmonize Islamic values with scientific approaches in order to make counseling services more relevant to modern society. This research uses a qualitative method with a descriptive-analytical approach that analyzes data to build a model of integrating the connections between Islamic teachings and psychology. The main sources of this research are prophetic traditions related to counseling practices and contemporary psychological literature. The results show that the integration of Islamic values through the prophetic traditions with modern psychological theories can produce a holistic approach to counseling. This model provides practical guidance for counselors to help clients overcome various life problems in both spiritual and psychological aspects through various methods such as: interview method, counseling method, and home visit method.